YTHDF2-mediated circYAP1 drives immune escape and cancer progression through activating YAP1/TCF4-PD-L1 axis - Zhuang Chen; Wenkang Wang; Shengyun Hu; Haifeng Sun; Chen Chen; Zhiyong Zhang; Xinzhi Sun; Bin Jia; Junhong Hu; Chengzeng Wang; Yang Liu; Zhenqiang Sun (iScience, 2024)
Summary: Immune escape is identified as one of the reasons for the poor prognosis of colorectal cancer (CRC) patients. Circular RNAs are considered to promote tumor progression by mediating tumor immune escape. We discovered that higher expression of circYAP1 was associated with a worse prognosis of CRC patients. Functional experiments in vitro and in vivo showed that circYAP1 upregulation inhibited the cytotoxicity of CD8+ T cells by upregulating programmed death ligand-1 (PD-L1). Mechanistically, we found that circYAP1 directly binds to the YAP1 protein to prevent its phosphorylation, enhancing proportion of YAP1 protein in the nucleus, and that YAP1 interacts with TCF4 to target the PD-L1 promoter and initiate PD-L1 transcription in CRC cells. Taken together, circYAP1 promotes CRC immune escape and tumor progression by activating the YAP1/TCF4-PD-L1 axis and may provide a new strategy for combination immunotherapy of CRC patients.